Tersesat di Jalan yang Benar dalam Pandangan Teologi Islam : Studi Atas Mahasiswa Salah Jurusan - El Syam, Robingun Suyud; Sunarko, Asep (DAS Institute, 2024)
Graduating on time is every student's dream, but the facts on the ground are that there are many factors that influence late graduation. This article aims to answer the research question of getting lost on the right path in the view of Islamic theology regarding the case of students in the wrong major. This research is a literature review of the phenomenon of students getting the wrong major. The findings show: getting lost on the right path means realizing that what you experienced was not wrong, after thinking it was wrong at first. According to Islamic theology, God's will must be for the good of his creatures. God's provisions are not bad, because the provisions of destiny exist more because of grace and wisdom. Pure evil only comes from the perpetrator of the action. This research contributes to future research directions in the field of Islamic theology. Research synergizes logical aspects of reality and sacred theological aspects.